Tracheostomy and mechanical ventilation weaning in children affected by respiratory virus according to a weaning protocol in a pediatric intensive care unit in Argentina: an observational restrospective trial - Frydman Judith; Gonzalez Crotti Patricia; Caprotta Gustavo (BMC, 2011)
Abstract We describe difficult weaning after prolonged mechanical ventilation in three tracheostomized children affected by respiratory virus infection. Although the spontaneous breathing trials were successful, the patients failed all extubations. Therefore a tracheostomy was performed and the weaning plan was begun. The strategy for weaning was the decrease of ventilation support combining pressure control ventilation (PCV) with increasing periods of continuous positive airway pressure + pressure support ventilation (CPAP + PSV) and then CPAP + PSV with increasing intervals of T-piece. They presented acute respiratory distress syndrome on admission with high requirements of mechanical ventilation (MV). Intervening factors in the capabilities and loads of the respiratory system were considered and optimized. The average MV time was 69 days and weaning time 31 days. We report satisfactory results within the context of a directed weaning protocol.